Yiqi Huoxue Recipe inhibits cardiomyocyte apoptosis caused by heart failure through Keap1/Nrf2/HIF-1α signaling pathway. Issue 1 (1st January 2021) - Hu, Ling; Xu, Yanan; Wang, Qian; Liu, Meijie; Meng, Linfeng; Yan, Dongyan; Hu, Huagang; Xiao, Minjia; Yin, Zhenzhen; Li, Ying; Kang, Xiaoping
ABSTRACT: Yiqi Huoxue Recipe (YHR) is commonly used in China to treat diseases such as heart failure (HF). It has been reported that YHR can treat HF and has a certain protective effect on myocardial cell damage. The purpose of this study is to determine the cardioprotective effects of YHR on HF-induced apoptosis and to clarify its mechanism of action. Oxygen glucose deprivation/recovery (OGD/R) induces H9C2 cell apoptosis model. Ligation of the left anterior descending artery (LAD) coronary artery can induce an animal model of HF. We found that YHR protected H9C2 cells from OGD/R-induced apoptosis, reduced the level of reactive oxygen species (ROS) in H9C2 cells, and increased the mitochondrial membrane potential in H9C2 cells. The results of in vivo animal experiments showed that in the HF model, YHR could reduce infarct area of heart tissue and cardiomyocyte apoptosis rate. YHR regulated the expression of key apoptotic molecules, including increasing the ratio of Bcl-2 and Bax, and reducing the expression of Kelch-like ECH-associated protein 1 (Keap1) and caspase-3. Interestingly, YHR also regulates the expression of NF-E2-related factor 2 (Nrf2) in the nucleus. In summary, YHR may provide cardioprotective effects in heart failure through inhibiting the Keap1/Nrf2/HIF-1α apoptosis pathway. Graphical Abstract: uf0001